MENINGKATKAN MOTIVASI BELAJAR SISWA MENGGUNAKAN ZEP QUIZ PADA PEMBELAJARAN INFORMATIKA DI SMP - Widyaningrum, Dhea; Azhar Ahmad Smaragdina; Dion Dwi Rizky; Yanuar Eko Ardiansyah; Francisca Anindya Mayta Prasasti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The primary objective of this study is to enhance students' learning motivation in the Informatics subject through the use of the interactive media platform, Zep Quiz. Adopting the Kemmis and McTaggart model, this research employed a Classroom Action Research (CAR) approach, conducted over 2 cycles. The study involved 30 seventh-grade students from class VII-1 at SMP Negeri 29 Malang. Data were collected using a learning motivation questionnaire and analyzed quantitatively using descriptive statistics by calculating the average motivation scores. Improvements in motivation were observed through the results of the questionnaire. The findings indicate that the majority of students showed an increase in learning motivation after participating in quiz-based learning using Zep Quiz. A comparison between cycles revealed an increase in the number of students in the high motivation category and a decrease in those in the low motivation category. Zep Quiz helped create a dynamic and competitive learning atmosphere, encouraging students to be more motivated and actively engaged in understanding the subject matter.